A friction material and its preparation method, brake pad and application
By using specific formulas and processes in friction materials, a friction material with high heat resistance and wear resistance is solved, and the problem of degradation of friction materials at high temperatures in the prior art is improved, and the heat decay performance and mechanical strength of friction materials are improved. , ensuring the stability and safety of the brake system.
Patent Information
- Application Number
- CN202411264639.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The friction performance of existing friction materials at high temperatures is degraded and the heat-resistant attenuation performance is insufficient, resulting in unstable performance of the brake system under different driving conditions, affecting the safety performance of the vehicle or track system.
Using specific formulas of substrate and friction block layers, including phenolic resin, aramid pulp, steel fiber, inorganic filler, copper powder, nanofiller, MoS2, MoSi2, metal powder, etc., through cold pressing molding, laser processing and plasma spraying heat The compression molding process forms a friction material with high heat and wear resistance.
Maintain good friction performance at high temperatures, extend service life, reduce wear rate, improve mechanical strength and structural stability, and ensure the safety performance of the brake system.
Smart Images

Figure CN118775467B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of friction materials, and in particular relates to a friction material and a preparation method thereof, a brake pad, and an application thereof. Background Art
[0002] Friction materials play a vital role in the braking system and transmission system of vehicles or rail systems, and their performance directly affects the safety performance of rails and vehicles. Ideal friction materials should have a stable friction coefficient to ensure that they can provide appropriate braking force under various driving conditions, avoid vehicle locking, tail swinging, skidding or rollover caused by excessively high friction coefficients, and also prevent insufficient braking caused by too low friction coefficients. At the same time, the thermal decay performance and service life of the material are also important indicators to measure its quality. Good thermal decay resistance can extend the service life of the material and reduce the cost and inconvenience caused by frequent replacement. Summary of the invention
[0003] The present invention overcomes the defects of the prior art and thus provides a friction material and a preparation method thereof, a brake pad, and an application thereof. The friction material prepared by the method has good heat-fading resistance and can still maintain good friction performance at high temperatures.
[0004] The present invention solves the above technical problems through the following technical solutions.
[0005] The present invention provides a friction material, comprising a substrate and a friction block layer;
[0006] The matrix comprises the following raw materials in parts by weight: 30 parts of phenolic resin, 10-18 parts of aramid pulp, 6-12 parts of steel fiber, 7-15 parts of inorganic filler, 6-9 parts of copper powder, and 2-6 parts of metal filler;
[0007] The friction block layer comprises the following raw materials in parts by mass: 30 parts of nano filler, 5-9 parts of MoS2, 7-13 parts of MoSi2, and 4-7 parts of metal powder;
[0008] The nano filler comprises 15 parts of nano Al2O3, 6 to 10 parts of nano Si3N4 and 5 to 9 parts of nano TiO2.
[0009] In the present invention, the matrix comprises the following raw materials in parts by mass: 30 parts of phenolic resin, 12-16 parts of aramid pulp, 8-10 parts of steel fiber, 9-15 parts of inorganic filler, 7-9 parts of copper powder, and 4-6 parts of metal filler.
[0010] In the present invention, the friction block layer includes the following raw materials in parts by mass: 30 parts of nanofiller, 6 to 8.5 parts of MoS2, 8 to 12 parts of MoSi2, and 5 to 7 parts of metal powder. Among them, MoS2, as a solid lubricant, its low friction coefficient characteristics help to improve the lubrication performance of the friction block layer, thereby reducing friction and wear at normal working temperature. On the other hand, MoSi2 is known for its excellent wear resistance and chemical stability at high temperatures, which can provide protection for MoS2 and prevent performance degradation due to wear or chemical erosion in high temperature environments. Therefore, the presence of MoSi2 can maintain the stability of MoS2 under high temperature conditions, and the combination of the characteristics of the two effectively reduces the wear rate under high temperature conditions.
[0011] In the present invention, the nano filler includes the following raw materials in parts by mass: 15 parts of nano Al2O3, 5-8 parts of nano Si3N4 and 6-9 parts of nano TiO2. Among them, the addition of nano Al2O3 can significantly improve the hardness and thermal stability of the composite material, making it have better friction and wear resistance; the addition of nano Si3N4 seeds promotes the growth of nano Si3N4 grains, thereby improving the fracture toughness of the ceramic; the addition of TiO2 can also effectively reduce the friction coefficient and enhance the bonding strength with the matrix. The addition of these nano fillers can improve the dispersibility and wear resistance of the material, while reducing noise problems.
[0012] In the present invention, the phenolic resin is a phenolic resin modified by butyral latex, such as model HK-906 and model HK-901.
[0013] In the present invention, the inorganic filler is at least one of barium sulfate, mica, mullite, barite, graphite and quartz.
[0014] In the present invention, the metal filler includes 1-4 parts of foamed iron powder and 0.5-2 parts of Ni powder. The foamed iron powder is usually added to increase viscosity and reduce brake noise; the Ni powder is usually added to enhance the fatigue resistance and durability of the matrix, but the addition of Ni to the matrix material is also to form a Ni3Al phase with the Al powder of the friction block layer, which can play a precipitation strengthening role, so that the matrix and the friction block layer are more closely combined.
[0015] In the present invention, the metal powder includes 3-5 parts of Sn powder and 1-3 parts of Al powder. The Sn powder is added to the friction block layer to form a self-lubricating and self-repairing film on the friction pair surface during the friction process; the Al powder, as a reinforcing phase particle, can achieve uniform distribution without impurities at the interface between the matrix and the reinforcing phase particles, which not only improves the mechanical properties of the material, but also enhances its anti-scratch ability.
[0016] In the present invention, the particle size of the nanofiller is ≤80 nm, preferably 20-60 nm, such as 20 nm, 40 nm or 60 nm.
[0017] Furthermore, the particle size (D50) of the nano-Si3N4 is 20 nm.
[0018] Furthermore, the particle size of the nano-Al2O3 is 20nm.
[0019] Furthermore, the particle size of the nano-TiO2 is 60nm.
[0020] Furthermore, the nano-TiO2 is of anatase type.
[0021] In the present invention, the mass ratio of the raw material of the substrate to the raw material of the friction block layer is 10:2-4, preferably 10:2.5-3.3.
[0022] In the present invention, the friction coefficient of the friction material at 20° C. is 0.42-0.53, preferably 0.427-0.511.
[0023] In the present invention, the coefficient of variation of the friction material at 100-350° C. is γ=0.810-0.93, preferably γ=0.810-0.926.
[0024] In the present invention, the compressive strength of the friction material is 448-477 MPa.
[0025] The present invention also provides a method for preparing the friction material as described above, comprising the following steps:
[0026] S1. The raw materials of the matrix are mixed, ground, sieved and dried to obtain a matrix mixture;
[0027] The raw materials of the friction block layer are mixed, ground, sieved and dried to obtain a friction block layer mixture;
[0028] S2. The matrix mixture is cold pressed and laser processed to obtain a compact;
[0029] S3. The friction block layer mixture is plasma sprayed on the surface of the compact, and then hot pressed to obtain the friction material;
[0030] The powder feeding rate of the plasma spraying is 180-240 mL / h.
[0031] In S1, the mesh size of the sieving is 300-350 meshes.
[0032] In S2, the temperature of the cold pressing is 70-100°C, preferably 80-90°C.
[0033] In S2, the cold pressing pressure is 60-80 MPa.
[0034] In S2, the holding time of the cold press forming is 60 to 200 seconds.
[0035] In S2, the power of the laser is 1500-1900 W, preferably 1500-1700 W. Laser processing can form micro-pits on the surface of the material, and can also increase surface stress and improve wear resistance.
[0036] In S2, the voltage of the plasma spraying is 75~90V.
[0037] In S2, the gases used in the plasma spraying are argon and nitrogen.
[0038] In S2, the powder feeding rate of the plasma spraying is 180-240 mL / h, preferably 180-200 mL / h.
[0039] In S3, the temperature of the hot pressing molding is 145-160°C, preferably 145-155°C.
[0040] In S3, the pressure of the hot pressing molding is 15-30 MPa, preferably 15-20 MPa.
[0041] In S3, the hot pressing molding time is 6 to 10 minutes.
[0042] A brake pad comprises the above-mentioned friction material, a backing plate, an adhesive, a base pad and a heat insulation layer.
[0043] The application of the friction material as mentioned above, the friction material obtained by the method for preparing the friction material as mentioned above, or the brake pad as mentioned above, the application is the application in the braking system, clutch and transmission system in vehicles and rail transportation.
[0044] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] 1. The matrix material of the present invention ensures that the membrane material has high mechanical strength and structural stability, thereby showing excellent durability when subjected to the force generated during braking. The addition of metal to the matrix and friction block layer is not only to improve the thermal conductivity, but also to increase the bonding of the two phases.
[0047] 2. The combination of nanofillers in the friction block layer of the present invention not only improves the overall heat resistance and wear resistance, but also helps reduce noise. In addition, the combination of MoS2 and MoSi2 in the friction block layer further optimizes the wear resistance and stability of the material at high temperatures. MoS2 provides good lubrication properties, while the high temperature stability and wear resistance of MoSi2 protect MoS2 from degradation of its performance at high temperatures.
[0048] 3. The preparation method adopted by the present invention first uses laser processing to form micro-pits on the surface of the substrate. The micro-pits not only increase the roughness of the substrate surface, but also improve the bonding force between the friction block layer and the substrate during spraying, thereby helping to form a tighter and more uniform friction block layer.
[0049] 4. The friction material prepared by the present invention has excellent mechanical properties and heat-fading resistance. The compressive strength of the friction material is 448-477 MPa; the coefficient of variation of the friction material at 100-350°C is γ=0.810-0.93, and in some preferred embodiments, γ=0.810-0.926; the friction coefficient of the friction material at 20°C is 0.42-0.53, and in some preferred embodiments, it is 0.427-0.511. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is the SEM image of the friction material prepared in Example 1.
[0051] Figure 2 This is the SEM image of the friction material prepared in Example 2.
[0052] Figure 3 This is the SEM image of the friction material prepared in Comparative Example 1.
[0053] Figure 4 This is the SEM image of the friction material prepared in Comparative Example 3.
[0054] Figure 5 This is the SEM image of the friction material prepared in Comparative Example 4. DETAILED DESCRIPTION
[0055] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0056] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0057] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60-120 and 80-110 is listed for a specific parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" represents that all real numbers between "0-5" have been fully listed herein, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0058] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0059] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0060] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0061] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0062] If not specifically stated, in the present invention, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0063] The raw material information used in the following examples and comparative examples is as shown in the following table, but is not limited to the following manufacturers or models, see Table 1.
[0064]
[0065] Example 1
[0066] 1. The friction material of this embodiment is as follows:
[0067] (1) The matrix is composed of the following raw materials in parts by weight: 30 parts of phenolic resin, 16 parts of aramid pulp, 8 parts of steel fiber, 14.8 parts of inorganic filler, 8.2 parts of copper powder and 5.8 parts of metal filler;
[0068] The phenolic resin is the butyl latex modified phenolic resin HK-906 produced by Jining Huakai Resin Co., Ltd.
[0069] Aramid pulp is DuPont 1F538 from the United States;
[0070] The inorganic filler is 8.5 parts of mullite and 6.3 parts of barite;
[0071] The metal filler is 3.6 parts of foamed iron powder and 2.2 parts of Ni powder;
[0072] (2) The friction block layer is composed of the following raw materials by weight: 30 parts of nanofiller, 8.3 parts of MoS2, 11.7 parts of MoSi2 and 6.9 parts of metal powder;
[0073] The nanofiller is 15 parts of nano-Al2O3, 8.5 parts of nano-Si3N4 and 6.5 parts of nano-TiO2;
[0074] The metal powder is 4.6 parts of Sn powder and 2.3 parts of Al powder.
[0075] (3) The mass ratio of the raw material of the substrate to the raw material of the friction block layer is 10:2.7.
[0076] 2. The preparation method of the friction material of this embodiment is as follows:
[0077] (1) grinding, sieving and drying the raw materials of the matrix to obtain a matrix mixture;
[0078] The raw materials of the friction block layer are mixed, ground, sieved and dried to obtain a friction block layer mixture;
[0079] The mixing and grinding adopts a planetary ball mill; the mesh number of the sieve is 300 mesh.
[0080] (2) The matrix mixture is cold pressed at 85°C and 75 MPa for 80 seconds and laser processed at 1500 W to obtain a compact.
[0081] (3) Plasma spraying the friction block layer mixture on the surface of the green compact with a current of 500 A, a voltage of 80 V, a nitrogen flow rate of 100 scfm, a hydrogen flow rate of 10 scfm, a powder feed rate of 200 mL / h, and a spraying distance of 80 mm;
[0082] Hot pressing: The friction material can be obtained by hot pressing at 150℃ and 20MPa for 10 minutes. Figure 1 .
[0083] Example 2
[0084] The difference between this embodiment and embodiment 1 is:
[0085] 1. The friction material of this embodiment is as follows:
[0086] (1) The matrix is composed of the following raw materials in parts by weight:
[0087] 30 parts of phenolic resin, 14.2 parts of aramid pulp, 10 parts of steel fiber, 9.8 parts of inorganic filler, 9 parts of copper powder and 5.8 parts of metal filler;
[0088] The phenolic resin is the butyl latex modified phenolic resin HK-901 produced by Jining Huakai Resin Co., Ltd.
[0089] Aramid pulp is DuPont 1F1710 from the United States;
[0090] The metal filler includes 4.2 parts of foamed iron powder and 1.6 parts of Ni powder;
[0091] The inorganic filler was 6.2 parts of barium sulfate, 2.3 parts of barite and 1.3 parts of quartz.
[0092] SEM of friction material Figure 2 .
[0093] Example 3
[0094] The difference between this embodiment and embodiment 1 is:
[0095] 1. The friction material of this embodiment is as follows:
[0096] (2) The friction block layer is composed of the following raw materials in parts by weight:
[0097] 30 parts of nanofiller, 6 parts of MoS2, 8.6 parts of MoSi2 and 6.1 parts of metal powder;
[0098] The nanofiller includes 15 parts of nano-Al2O3, 9.8 parts of nano-Si3N4 and 5.2 parts of nano-TiO2;
[0099] The metal powder includes 3.8 parts of Sn powder and 2.3 parts of Al powder.
[0100] (3) The mass ratio of the raw material of the substrate to the raw material of the friction block layer is 10:3.3.
[0101] Example 4
[0102] The difference between this embodiment and embodiment 1 is:
[0103] 2. The preparation method of the friction material of this embodiment is as follows:
[0104] The matrix mixture was cold pressed at 70°C and 80MPa for 60s and laser processed at 1500W to obtain a compact.
[0105] Example 5
[0106] The difference between this embodiment and embodiment 1 is:
[0107] (3) Plasma spraying: powder feeding rate 220mL / h;
[0108] Hot pressing: The friction material can be obtained by hot pressing at a temperature of 155°C and a pressure of 15 MPa for 8 minutes.
[0109] Comparative Example 1
[0110] The friction block layer raw material of this comparative example does not contain MoSi2 and MoS2.
[0111] The difference between this comparative example and Example 1 is:
[0112] 1. The friction materials of this comparative example are as follows:
[0113] The friction block layer is composed of the following raw materials in parts by mass: 30 parts of nanofiller, 8.3 parts of MoS2 and 6.9 parts of metal powder.
[0114] SEM of friction material Figure 3 .
[0115] Comparative Example 2
[0116] The nano filler in this comparative example contains only nano Al2O3, and does not contain nano Si3N4 and nano TiO2.
[0117] The difference between this comparative example and Example 1 is:
[0118] 1. The friction materials of this comparative example are as follows:
[0119] The nano filler is 15 parts of nano Al2O3.
[0120] Comparative Example 3
[0121] This comparative example does not contain a friction block layer.
[0122] The difference between this comparative example and Example 1 is:
[0123] 1. The friction materials of this comparative example are as follows:
[0124] (1) This comparative example consists only of the base material of Example 1.
[0125] 2. The preparation method of the friction material of this comparative example is as follows:
[0126] (1) No need to prepare the friction block layer mixture;
[0127] (3) The compact is directly sintered without plasma spraying.
[0128] SEM of friction material Figure 4 .
[0129] Comparative Example 4
[0130] The difference between this comparative example and Example 1 is:
[0131] 2. The preparation method of the friction material of this embodiment is as follows:
[0132] Powder feeding rate: 300 mL / h.
[0133] SEM of friction material Figure 5 .
[0134] Effect Example
[0135] The performance results of the above examples and comparative examples are shown in Table 2.
[0136] At 20°C, the static friction coefficient μ is tested by a testing machine. The two test surfaces are placed flat and tightly fitted. The static friction coefficient μ can be calculated by dividing the measured static friction force f by the normal force N, and the result is the average of three test results. The static friction force f is measured by a tension sensor installed on the testing machine.
[0137] Coefficient of variation γ = μ min / μ max , μ min and μ maxThey are the minimum and maximum values of the static friction coefficient measured 5 times at different temperatures. The variation coefficient γ can reflect the friction performance of the material at different temperatures. The closer the variation coefficient γ is to 1, the better the heat-fading resistance of the friction material at this temperature.
[0138]
[0139] It can be clearly seen from the analysis of Table 2 and the accompanying drawings that the surfaces of the friction materials of Examples 1 and 2 exhibit a uniformly distributed pit structure.
[0140] In contrast, the static friction material in Comparative Example 1 has a small change in friction coefficient at high temperature due to the absence of MoSi2, and its γ value drops sharply at 300°C, indicating that its thermal stability is poor. In addition, the distribution of protrusions and pits in the friction block layer of Comparative Example 1 is uneven, which may affect the consistency and reliability of the material.
[0141] In Comparative Example 2, since the filler of the friction block layer lacks nano-Si3N4 and nano-TiO2, its compressive strength is significantly reduced.
[0142] The friction material of comparative example 3 lacks a friction block layer, so its friction coefficient is low and its friction performance is poor. At the same time, there are large crack defects on the local surface of this material.
[0143] In Comparative Example 4, since the plasma spraying rate is too high, the coating cannot be uniformly formed on the substrate, and the resulting pits are smaller and less in number, which also leads to a decrease in the static friction coefficient.
[0144] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A friction material, characterized in that: including a substrate and a friction block layer; The matrix comprises the following raw materials in parts by weight: 30 parts of phenolic resin, 10-18 parts of aramid pulp, 6-12 parts of steel fiber, 7-15 parts of inorganic filler, 6-9 parts of copper powder, and 2-6 parts of metal filler; The friction block layer comprises the following raw materials in parts by mass: 30 parts of nano filler, 5-9 parts of MoS2, 7-13 parts of MoSi2, and 4-7 parts of metal powder; The nano filler includes 15 parts of nano Al2O3, 6-10 parts of nano Si3N4 and 5-9 parts of nano TiO2; The friction coefficient of the friction material is 0.42-0.53 at 20°C; The coefficient of variation of the friction material at 100-350° C. is γ=0.81-0.93; The compressive strength of the friction material is 448-477 MPa.
2. The friction material according to claim 1, characterized in that: Satisfy at least one of the following conditions a~e: a. The phenolic resin is a phenolic resin modified with butyral latex; b. The inorganic filler is at least one of barium sulfate, mica, mullite, barite, graphite and quartz; c. The metal filler comprises 1 to 4 parts of foamed iron powder and 0.5 to 2 parts of Ni powder; d. The metal powder comprises 3 to 5 parts of Sn powder and 1 to 3 parts of Al powder; e. The particle size of the nanofiller is ≤80nm.
3. The friction material according to claim 1, characterized in that: The mass ratio of the raw material of the substrate to the raw material of the friction block layer is 10:2-4.
4. The method for preparing the friction material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. The raw materials of the matrix are mixed, ground, sieved and dried to obtain a matrix mixture; The raw materials of the friction block layer are mixed, ground, sieved and dried to obtain a friction block layer mixture; S2. The matrix mixture is cold pressed and laser processed to obtain a compact; S3. The friction block layer mixture is plasma sprayed on the surface of the compact, and then hot pressed to obtain the friction material; The powder feeding rate of the plasma spraying is 180-240 mL / h.
5. The method for preparing the friction material according to claim 4, characterized in that: The cold press forming satisfies at least one of the following conditions a to c: a. The cold pressing temperature is 70~100℃; b. The cold forming pressure is 60~80MPa; c. The holding time of the cold pressing molding is 60 to 200 seconds.
6. The method for preparing the friction material according to claim 4, characterized in that: Satisfy at least one of the following conditions a~c: a. The laser power is 1500~1900W; b. The voltage of the plasma spraying is 75~90V; c. The gases used in the plasma spraying are argon and nitrogen.
7. The method for preparing the friction material according to claim 4, characterized in that: The hot pressing molding satisfies at least one of the following conditions a to c: a. The temperature of the hot pressing molding is 145~160℃; b. The hot pressing pressure is 15~30MPa; c. The hot pressing time is 6 to 10 minutes.
8. A brake pad, characterized in that: The invention comprises the friction material as claimed in any one of claims 1 to 3, a backing plate, an adhesive, a base pad and a heat insulation layer.
9. Use of the friction material according to any one of claims 1 to 3 or the friction material obtained by the method for preparing the friction material according to any one of claims 4 to 7, characterized in that: The applications are applications in brake systems, clutches and transmission systems in vehicles and rail transport.
